GENDER DALAM TATA KELOLA PERUSAHAAN : AKANKAH MEMPERSINGKAT AUDIT DELAY? - Muhammad Agil Trianto; Melisa Anggraini (LPPM STIE Muhammadiah Bandung, 2025)
Governance in a company is a system used by a firm to keep its operations sustainable. One of the important elements of corporate governance is gender diversity in the corporate governance structure, including the board of directors, audit committee, and CEO gender. The purpose of this research is to determine if audit delays are affected by gender diversity in corporate governance. Utilizing quantitative methodologies and secondary data, this study puts the idea to the test. Secondary data comes from the Indonesia Stock Exchange-listed financial accounts of the manufacturing company from 2021–2024. Female chief executive officers, female representation on boards of directors, and audit committee diversity are the three independent variables in this study. The data was examined using multiple regression analysis, using the audit delay as the dependent variable. The results of this research suggest that gender diversity in the audit committee, the number of women on the board of directors, and the existence of female CEOs had no effect on audit delays.